Detection of myocardial viability based on measurement of sodium content: A (23)Na-NMR study. - Horn, M; Weidensteiner, C; Scheffer, H; Meininger, M; de Groot, M; Remkes, H; Dienesch, C; Przyklenk, K; von Kienlin, M; Neubauer, S (2001)
MRI of total sodium (Na) content may allow assessment of myocardial viability, but information on Na content in normal myocardium, necrotic/scar tissue, and stunned or hibernating myocardium is lacking. Thus, the aims of the study were to: 1) quantify the temporal changes in myocardial Na content post-myocardial infarction (MI) in a rat model (Protocol 1); 2) compare Na in normally perfused, hibernating, and stunned canine myocardium (Protocol 2); and 3) determine whether, in buffer-perfused rat hearts, infarct scar can be differentiated from intact myocardium by (23)Na-MRI (Protocol 3). In Protocol 1, rats were subjected to LAD ligation. Infarct/scar tissue was excised at control and 1, 3, 7, 28, 56, and 128 days post-MI (N = 6-8 each), Na content was determined by (23)Na-NMR spectroscopy (MRS) and ion chromatography. Na content was persistently increased at all time points post-MI averaging 306*-160*% of control values (*P < 0.0083 vs. control). In Protocol 2, (23)Na-MRS of control (baseline), stunned and hibernating samples revealed no difference in Na. In Protocol 3, (23)Na-MRI revealed a mean increase in signal intensity, to 142 +/- 6% of control values, in scar tissue. A threshold of 2 standard deviations of the image intensity allowed determination of infarct size, correlating with histologically determined infarct size (r = 0.91, P < 0.0001).